Customer Satisfaction, Revisit Intention and Word of Mouth in the Restaurant Business - Pun, Lal Bahadur (Butwal Campus Journal, 2022)
Restaurant businesses were hard hit by the pandemic over the last few years. The prolonging situation calls for appropriate remedial considerations. This paper attempts to predict the revisit intention and word-of-mouth using customer satisfaction. The data from 399 respondents were collected using mail survey immediately after the hit of COVID-19. Firstly, the result from linear regression of customer satisfaction on their revisit intention suggests that the customer satisfaction is the crux of customer retention in restaurant business. Secondly, the logistic regression of customer satisfaction on word-of-mouth reveals that word-of-mouth is likely to take place when the customers are dissatisfied with the restaurant services. Contrary to this, word-of-mouth communication is less likely to happen when the customers are happy with the restaurant services.